HIV-1 proviral DNA in purified peripheral blood CD34+ stem and progenitor cells in individuals with long-term HAART; paving the way to HIV gene therapy - Boonrat Tassaneetrithep; Angsana Phuphuakrat; Ekawat Pasomsub; Kanit Bhukhai; Wasinee Wongkummool; Thongkoon Priengprom; Wannisa Khamaikawin; Sujittra Chaisavaneeyakorn; Usanarat Anurathapan; Nopporn Apiwattanakul; Suradej Hongeng (My University, 2024)
Human immunodeficiency virus (HIV)-1 infection is an important public health problem worldwide. After primary HIV-1 infection, transcribed HIV-1 DNA is integrated into the host genome, serving as a reservoir of the virus and hindering a definite cure. Although highly active antiretroviral therapy suppresses active viral replication, resulting in undetectable levels of HIV RNA in the blood, a viral rebound can be detected after a few weeks of treatment interruption. This supports the concept that there is a stable HIV-1 reservoir in people living with HIV-1. Recently, a few individuals with HIV infection were reported to be probably cured by hematopoietic stem transplantation (HSCT). The underlying mechanism for this success involved transfusion of uninfected hematopoietic stem and progenitor cells (HSPCs) from CCR5-mutated donors who were naturally resistant to HIV infection. Thus, gene editing technology to provide HIV-resistant HSPC has promise in the treatment of HIV infections by HSCT. In this study, we aimed to find HIV-infected individuals likely to achieve a definite cure via gene editing HSCT. We screened for total HIV proviral DNA by Alu PCR in peripheral blood mononuclear cells (PBMCs) of 20 HIV-infected individuals with prolonged viral suppression. We assessed the amount of intact proviral DNA via a modified intact proviral DNA assay (IPDA) in purified peripheral CD34
Keywords: Provirus; HIV Research and Treatment